Preceptorship-Mentor Model Approach Training At Balangan Regional General Hospital - Yustan Azidin; Evy Noorhasanah; Anita Agustina; Milasari; Metti Agustini; Yosra Sigit Pramono; Ica Lisnawati (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
Attempting to develop and control the quality of nursing education embodied by developing a field of nursing practice accompanied by nursing resources development for which carry out learning experiences properly. One of which is administer preceptorship training for both academic and clinical preceptors to be able to provide a proper mentoring process. It is expected that the students competency could be achieved. This preceptorship training aims to upgrade the mentoring process. This training used the Preceptorship-mentor model approach and held for 2 days at the Regional General Hospital Balangan with a total of 25 participants. Training methods use lectures, discussions and role plays. The evaluation were carried out by means of a pre and post test. The conclusion: participants knowledge about preceptorship and mentorship increased after following the training. It is expected that the institution of nurse education could be provide preceptorship training regularly to develop quality of nursing education.